Leveraging HST with MUSE: II. Na-abundance variations in intermediate age star clusters. Issue 1 (24th September 2020) - Martocchia, S; Kamann, S; Saracino, S; Usher, C; Bastian, N; Rejkuba, M; Latour, M; Lardo, C; Cabrera-Ziri, I; Dreizler, S; Kacharov, N; Kozhurina-Platais, V; et al.
ABSTRACT: Ancient (>10 Gyr) globular clusters (GCs) show chemical abundance variations in the form of patterns among certain elements, e.g. N correlates with Na and anticorrelates with O. Recently, N abundance spreads have also been observed in massive star clusters that are significantly younger than old GCs, down to an age of ∼2 Gyr. However, so far N has been the only element found to vary in such young objects. We report here the presence of Na abundance variations in the intermediate age massive star clusters NGC 416 (∼6.5 Gyr old) and Lindsay 1 (∼7.5 Gyr old) in the Small Magellanic Cloud, by combining Hubble Space Telescope ( HST) and European Southern Observatory Very Large Telescope MUSE observations. Using HST photometry, we were able to construct 'chromosome maps' and separate subpopulations with different N content, in the red giant branch of each cluster. MUSE spectra of individual stars belonging to each population were combined, resulting in high signal-to-noise spectra representative of each population, which were compared to search for mean differences in Na. We find a mean abundance variation of Δ[Na/Fe] = 0.18 ± 0.04 dex for NGC 416 and Δ[Na/Fe] = 0.24 ± 0.05 dex for Lindsay 1. In both clusters, we find that the population that is enhanced in N is also enhanced in Na, which is the same pattern to the one observed in ancient GCs. Furthermore, we detect a bimodal distribution of core-helium-burning red clump (RC) giants in the UV colour–magnitude diagram of NGC 416. A comparison of the stacked MUSE spectra of the two RCs shows the same mean Na abundance difference between the two populations. The results reported in this work are a crucial hint that star clusters of a large age range share the same origin: they are the same types of objects, but only separated in age.